A Case Report on Comparitive Therapeutic Effect of Transdermal Patches of Ketoprofen with that of Fentanyl in Pain Control - Heera Battu; Nimmathota Madhavi; Mecca Subhakaram (Current Innovations in Medicine and Medical Science Vol. 5, 2022)
Many patients will not be relieved of their symptoms after surgery because the therapeutic efficacy of the drug varies from patient to patient. The goal of this case report is to compare the therapeutic efficacy of two patches, ketoprofen and fentanyl, in post-operative patients. We present a case report on the extent of pain relief compared with visual analogue scale scores (VAS score) after post-operative surgery other than spine surgery using ketoprofen transdermal patch and fentanyl transdermal patch on patients. The subjects were divided into two groups, male and female, and the treatment was given for up to three days. After completing the study, we concluded that the subjects who received ketoprofen therapy had the highest VAS score when compared to those who received fentanyl therapy, and complete pain relief was observed in three days. The statistical analysis revealed that it was highly significant.